2003
DOI: 10.1002/art.10709
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of peroxisome proliferator–activated receptor γ expression in human monocytes by monosodium urate monohydrate crystals

Abstract: Objective. Peroxisome proliferator-activated receptor ␥ (PPAR␥) is a member of the nuclear hormone receptor superfamily and functions as a key regulator of lipid and glucose metabolism, atherosclerosis, and inflammatory responses. This study was undertaken to evaluate the biologic role of PPAR␥ in self-limiting episodes of acute gouty arthritis. To do this, we investigated PPAR␥ expression by monosodium urate monohydrate (MSU) crystal-stimulated monocytes, and we studied the effects of PPAR␥ ligands on crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 37 publications
3
55
0
1
Order By: Relevance
“…Monosodium urate crystals were prepared according to a previously published method. 21 Briefly, 800 mg uric acid was dissolved in 155 ml boiling distilled water containing 5 ml of 1 mol/l NaOH. After the pH of the solution was adjusted to 7.2 by the addition of 1 mol/l HCl, the solution was cooled gradually with stirring at room temperature and then stored overnight at 4 uC.…”
Section: Reagentsmentioning
confidence: 99%
“…Monosodium urate crystals were prepared according to a previously published method. 21 Briefly, 800 mg uric acid was dissolved in 155 ml boiling distilled water containing 5 ml of 1 mol/l NaOH. After the pH of the solution was adjusted to 7.2 by the addition of 1 mol/l HCl, the solution was cooled gradually with stirring at room temperature and then stored overnight at 4 uC.…”
Section: Reagentsmentioning
confidence: 99%
“…Importantly, activation of PPAR␥ by naturally occurring ligands also appears to have antiinflammatory effects. In the joint, for example, monosodium urate monohydrate crystals have been shown to activate PPAR␥ on monocytes, presumably via endogenous 15d-PGJ 2 , and crystal-induced PPAR␥ activation was implicated as a potential mechanism to explain the spontaneous resolution of acute inflammation associated with gouty arthritis (21). In light of its potent antiinflammatory effects, PPAR␥ ligands hold substantial promise as novel immunomodulatory and antiinflammatory agents.…”
mentioning
confidence: 99%
“…Treatment with PKA stimulators markedly increased PPARg activity (Akahoshi et al 2003). Interestingly, Liu et al (2009) also found cAMP/PKA signals could induce TR4 expression by triggering C/EBPa and b binding to the selective cAMP response elements located on the TR4 promoter that leads to the modulation of gluconeogenesis.…”
Section: Phosphorylationmentioning
confidence: 94%